2019
DOI: 10.15282/jmes.13.4.2019.11.0467
|View full text |Cite
|
Sign up to set email alerts
|

Emission and vibration characteristics of Niger seed oil biodiesel fueled diesel engine

Abstract: The present investigation dwells the experimental investigation for the assessment of emission, vibration, and noise parameters of single-cylinder, DI diesel engine functioning through the blends of conventional diesel and Niger seed oil methyl ester (NSOME) at different engine operating loads namely 25%, 50%, 75%, and 100% at a constant speed. The carbon monoxide (CO), unburnt hydrocarbons (UHC), and smoke opacity emissions have come down significantly for all the blends of NSOME namely B10, B20, and B40 whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…This study examined the optimization of noise reduction at the engine and its exhaust with biodiesel blend, load, and compression ratio of the engine as input parameters. Analysis was carried out utilizing the Taguchi method, and optimization of the input parameters was performed by using SNR [10,11]. The experimental results obtained by Minitab were validated by an ANN.…”
Section: Discussionmentioning
confidence: 99%
“…This study examined the optimization of noise reduction at the engine and its exhaust with biodiesel blend, load, and compression ratio of the engine as input parameters. Analysis was carried out utilizing the Taguchi method, and optimization of the input parameters was performed by using SNR [10,11]. The experimental results obtained by Minitab were validated by an ANN.…”
Section: Discussionmentioning
confidence: 99%
“…The vibration signature was noticed less for biodiesel fuel blends than ordinary diesel oil. Since the combustion effectiveness of biodiesel blends were superior to neat diesel fuel as a result of having greater cetane number (fuel quality), lower delay in the ignition, and a lot of oxygen accessibility [20,21]. Thus, the total burning happens and results in the lesser tendency of knock.…”
Section: Time Domain Vibration Characteristicsmentioning
confidence: 99%
“…6 RMS noise at different FIPs biodiesel. This results in an inferior propensity of knock and thus the noise was reduced [20,21,23]. Besides, a fall down in noise intensity was observed at rising FIP.…”
Section: Frequency Domain Noise Characteristicsmentioning
confidence: 99%
“…Due to the overwhelming increase in petrol fuels demand globally, the search for alternatives fuels is critical to avoid the scarcity of fuel source. Biodiesel, as an alternative to fossil fuels, can be utilized as vehicle fuel without major modification in diesel engine [3,4]. Biodiesel is the most promising alternative for vehicle fuel as studies reported that biodiesel is environmentally friendly, easily biodegradable and renewable [5,6].…”
Section: Introductionmentioning
confidence: 99%